Experiences of radiographers working alone in remote locations: A Far North Queensland non-participant observational study. Issue 4 (November 2020) - Williams, I.; Baird, M.; Schneider, M.
Abstract: Introduction: Radiographers employed in remote locations such as Far North Queensland (FNQ) can face unique sets of challenges as they often perform radiographic and sonographic diagnostic imaging without onsite radiologists' services. Additionally, the majority of patients presenting to these sites are Indigenous for whom English may be their third language. This non-participant observational study observed two FNQ radiographers' interactions with patients and interprofessional staff, and the radiographers' ability to fit into the Indigenous community during routine radiographic and sonographic examinations which to date have received little attention. Methods: Non-participant observations and semi-structured interviews with radiographers were held at two FNQ hospitals. Consecutive radiographer–patient interactions were observed and recorded on checklists. Interviews were audio recorded and transcribed for thematic analysis. Results: Across both remote sites, 24 patients were observed as they underwent diagnostic imaging examinations, with the majority being Aboriginal or Torres Strait Islanders (n = 17/24 (70.8%). In total, eleven general radiography and sixteen ultrasound examinations were observed. Semi-structured interviews highlighted complex issues such as the need for radiographer communication in local dialect, ongoing interprofessional collaborations, overcoming the lack of radiologists' onsite support by providing radiographic reports directly to referring doctors and midwives, and isolation with regard to professional development opportunities. Conclusions: Radiographers working in remote hospitals need to be culturally competent, navigate local indigenous languages and possess excellent interprofessional skills as well as thorough knowledge of imaging pathology to convey findings to referring doctors and allied health professionals. These findings have implications for the entry to practice curriculum. Implications for practice: This study provides evidence that culturally competent radiographers are capable of undertaking reporting roles to facilitate patient management in the absence of timely radiologists' reports at remote sites.